“evaluación del efecto de dosis con enmienda calcio magnesia en el rendimiento del cultivo de maní (arachis hypogaea) en el suelo acido del fundo aucaloma” - Pezo Perea, Max Beltrán (2002)
This research work was carried out in the Aucaloma's experimental field of the UNSM County of Lamas San Martin (Perú) geographically located at 6º29' South latitude 76º 21' West longitude and 650 mt.s.l.o. (sea level over). To evaluate the effect of amends calcium magnesica 15 doses in the yield of the peanut crops and to carry out the beast treatments economic analysis was the experimental means. The statistical design of randomized complete block was used with four repetitions and 15 treatments. To check the studied variables, the variance analysis and the 0.05 % probability Duncan test was used. The floor characteristics were> sandy franc texture, sour reaction (pH = 5. 72) half content of organic matter (3.22%) wilt phosphorus readiness (12 pfm) lower content of interchangeable cations an saturation of high relatively aluminum (67.5%). Those: o.o, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, and 7.0 TM/Ha of amends calcium magnesica were the evaluated treatments. From the results we concludes that it was highly significant differences for the diversa applied doses showing in the increased grain yield, standing out the T15, T12, T7 (7.0, 5.5 and 3.0 TM/Ha) treatments with 2508, 2332 and 2292 yields. Likewise the best economic benefit was obtained with the T7 (3. o TM/Ha) treatment whose which relationship B/C was 1.24. lt was not significant difference for the plant height parameter in none of treatments. With regard of the floor chemical characteristics, it was highly significant differences as for the pH levels, phosphorus, potassium, calcium Magnesium and so much Aluminum to the moment of the sow like the crop; it was observad an increment of the pH and the diversa evaluated nutrients and in the other a decrease of the increase of the applied amends calcium magnesica doses being the superior dose 5.0 TM/Ha those which neutralizad totally to the interchangeable aluminum.